Pionowe zróżnicowanie bioty porostów na pniu jesionu wyniosłego Fraxinus excelsior oraz znaczenie tego drzewa w zachowaniu różnorodności gatunkowej porostów w rezerwacie Oleszno (Przedborski Park Krajobrazowy) - Łubek, Anna (Leśne Prace Badawcze, 2012)
A lichenological study was carried out in the Oleszno reserve and in its surroundings on Fraxinus excelsior trees uprooted by the wind. They have created the opportunity to examine biota over its entire length, especially in the crown. The main aim of this work was to present the diversity of epiphytic lichen species occurring on the bark of Fraxinus excelsior. Lichen species were censured at three different heights on the trunk: 0-50 cm and 50-200 cm from the ground, and in the crown. The study identified the remaining available habitats and substrates for lichens, finding that there were 133 species of lichens, of which 109 occurred on the bark of Fraxinus excelsior. Most epiphytes were found in the crown of trees (66 species), and the fewest at the base of the trunk (52 species). Foliose and fruticose lichens were more common in the crown of trees than on the trunk or base. The crown of Fraxinus excelsior was notable in having the highest proportion of exclusive species. 87% of species of lichens found on the bark of the trees are threatened and some of them are recorded only in the study area. 26 species of lichens are under the strict and partial protection. The cracked bark of old Fraxinus excelsior specimens is the place where many rare and stenotopic lichen species in Poland occur. It plays a significant role in preserving the rich and valuable epiphytic lichen biota.